THE CONSTRUCTION OF NANDAK ZABET TAK-TUNG DANCE: ADAPTATION OF ZAPIN AND SAMRAH MOVEMENTS WITHIN THE ARABMALAY PERANAKAN CULTURAL CONTEXT : THE CONSTRUCTION OF NANDAK ZABET TAK-TUNG DANCE: ADAPTATION OF ZAPIN AND SAMRAH MOVEMENTS WITHIN THE ARABMALAY PERANAKAN CULTURAL CONTEXT - Soewardjo, B Kristiono; Andriyanto, Raden Mas Aditya; Oktarini , Selly; Sudiasa, Ida Bagus Ketut (International Journal of Performing Arts (IJPA), 2025)
This study analyzes dance as a medium of cultural acculturation through the creation of NandakZabet Tak-Tung, rooted in the Betawi cultural framework. It focuses on adapting Zapin and Samrahmovements to represent Arab-Malay Peranakan heritage, while exploring interdisciplinaryconnections with music, scenography, and other artistic elements. The research employs a qualitativemethod with systematic stages: defining focus, collecting data via direct observation, in-depthinterviews, and document analysis. Data are organized into a structured matrix to supportinterpretation.The theoretical foundation draws from Alma M. Hawkins’ creative concept in Moving from Within,translated by I Wayan Dibia, encompassing six aspects: experiencing, seeing, feeling, imagining,transforming, and forming. These guide the choreographic process, resulting in a work thatreconfigures Zapin and Samrah into a dynamic structure emphasizing movement exploration andembodiment.Through imaginative choreography inspired by local traditions, the study proposes the use of ArabMalay Peranakan-based movement to enrich Betawi dance. It contributes to the preservation andinnovation of Indonesian performing arts by integrating cultural heritage with contemporaryexpression. Ultimately, this research supports the advancement of knowledge, technology, and sociocultural development within a humanistic and locally grounded artistic landscape.